(3GdehahQ ef TQM GHf YUahQs - (3CHhMjGf eMeO Hf jhSa GdZQfGWis; (3GHf YUahQ , Ydj Hf eDef Hf eMeO GdMVQej GdGTHjdj, CHh GdMSf,J (B669 (3g` s
(3BNQgG (B:s
(3HGdcdGe Ydi CSeGA GdaGYd hGdeaYhd s
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B27s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B17 - (3U (B399 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1805s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdfMhs